Dari Transaksi hingga Laporan Keuangan: Peran Akuntansi dalam Pengelolaan Pendapatan Hotel - Herlivanezra Lalu; Paradisa Sukma; Putu Erlianti (Jurnal Riset Mahasiswa Akuntansi, 2026)
Revenue management is one of the important processes in hotel operations because it affects the accuracy of the financial information produced. This article aims to explain the flow of hotel revenue management and examine the role of the accounting department in maintaining the reliability of financial information. The article was written using a descriptive method with a direct observation approach during an internship program in the accounting department at a star-rated hotel. Data were obtained through observation of operational activities, documentation, and direct involvement in the hotel revenue management process. The analysis was conducted descriptively by comparing field practices with the concepts of revenue management and internal control found in the literature.The results show that each revenue transaction does not directly become part of the financial statements but must go through several stages, including recording by department cashiers, verification by Income Audit, processing by the General Cashier or Accounts Receivable, and recording in the accounting system before being presented in financial reports. In addition, it was found that human error in transaction input is one of the most frequent obstacles, making adequate internal control necessary. Therefore, the accounting department plays an important role in producing financial information that is accurate, reliable, and supports the effectiveness of hotel operations.